The religious aspects of Turkic dastans (Journal of Oriental Studies, 2018)
This article seeks to examine the influence of religious motives in Turkishdastans, especially the example of «Қissa Hazіret Zhүsіp ӘleyһissalamIlәn Zylihanyң mәselesі».The author explores the religious aspects of theconceptual – semantic vision based on three main books: Ғashyқ – Namе,the Holy Quran and the Bible. An author analyses connections and cooperationof one personage: his fate and historical meaningfulness on thejoint of two religions. There are comparison of role of personage from theside of mental and ethical values and influence of succession in turkicdastans.